Passport : exchange (ex)change. (Warszawa : Galeria Zacheta, 1998)
Althamer, Pawel ; Cullen, Shane ; Golec, Leszek ; Czekalska, Tatiana ; Gomulicki, Maurycy ; Jones, Finola ; Koza, Janek ; McCarthy, Caroline ; McCrea, Ronan ; Myca, Anna ; O'Brien, Abigail ; O'Connell, Maurice ; Orchard, Kate ; Sims, Theo ; Sztwiertnia, Grzegorz ; Wilson, Mick ; Woszczynski, Mariusz ; Zmijewski, Artur
Pools & Engels
Bez paszportu / Passport : exchange (ex)change, Galeria Sztuki Wspólczesnej Zacheta, Warszawa, 18.07 - 16.08.1998
kunstcatalogus